Multifunctionality of green corridors during pandemic lockdowns: a case study of Riobamba city in Ecuador (International Journal of Scientific Research and Management (IJSRM), 2022)
The pandemic has demonstrated several weaknesses and inequalities in the way society live and develops within cities, such as economic losses, massive contagions, and above all, the lack of control and people’s lack of awareness about the crisis. This study aims to investigate the transformation of cities with a shortage of green spaces into cities with green and sustainable planning, the association between urban greenery and physical activity during the Covid-19, and urban green corridors as a planning tool for urban green areas. The green corridor was born out of a social need in the face of a health crisis and the improvement of the urban environment. This research employs three methods to study: empirical judgment and experience analysis and network analysis. All those who could not cope with the lockdown exposed green and recreational spaces in Riobamba, since only 7% of those surveyed stayed at home, while 70% left their homes for green or recreational spaces within the urban area and 23% left the city. This shows how the quality of green areas can positively affect people’s behaviors during the Covid-19. This effect highlighted the preservation of natural areas, urban reforestation, and re-naturalization of spaces. The urban green corridor is a system that connects several spaces, creating two interactions: the first is how the city can provide the necessary infrastructure during a crisis, and the second is how it energizes and prioritizes the health and supply systems for urban residents, creating safe spaces for each of the city’s sectors.